2011
DOI: 10.1002/spe.1112
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting bounded context block‐sorting transformations

Abstract: The Burrows-Wheeler Transform (BWT) produces a permutation of a string X, denoted X , by sorting the n cyclic rotations of X into full lexicographical order and taking the last column of the resulting n n matrix to be X . The transformation is reversible in O.n/ time. In this paper, we consider an alteration to the process, called k-BWT, where rotations are only sorted to a depth k. We propose new approaches to the forward and reverse transform, and show that the methods are efficient in practice. More than a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In [28] Schindler proposes a bounded context transformation that differs from the BWT in the fact that the rotations are lexicographically sorted considering only the first symbols of each rotation. Recent studies [6,27] have shown that this variant satisfies properties 1-3, with the limitation that the compression ratio can reach at maximum the -th order entropy and that it supports searches of patterns of length at most . Chapin and Tate [3] have experimented with computing the BWT using a different alphabet order.…”
Section: Known Bwt Variantsmentioning
confidence: 98%
“…In [28] Schindler proposes a bounded context transformation that differs from the BWT in the fact that the rotations are lexicographically sorted considering only the first symbols of each rotation. Recent studies [6,27] have shown that this variant satisfies properties 1-3, with the limitation that the compression ratio can reach at maximum the -th order entropy and that it supports searches of patterns of length at most . Chapin and Tate [3] have experimented with computing the BWT using a different alphabet order.…”
Section: Known Bwt Variantsmentioning
confidence: 98%
“…Interestingly, although the additional cost of recovering the context group is asymptotically worse than in the full BWT, T can be recovered faster from T k-BWT than from T BWT due to the sequential access of each context group. The sequential access results in a significant cache effect not present in the random jumps induced by the BWT [4].…”
Section: Text Transformationsmentioning
confidence: 99%
“…This guarantees a worst case runtime complexity of O(kmaxn). In practice small values for the parameter k allow the bounded sorting depth transform to perform faster than full suffix array construction algorithms [4].…”
Section: The Variable Depth Transformmentioning
confidence: 99%
“…To consistently determine the correct context bounds, a bitvector D k is required in order to reconstruct T from [24] or it can be stored with T k-BWT at a cost of n bits. These and other trade-offs are explored in [25].…”
Section: The Burrows-wheeler Transformmentioning
confidence: 99%